Lets’ Shopping App / Syed Muhammad Murshid Syed Zubir - Syed Zubir, Syed Muhammad Murshid (2020)
Staying ahead and following the changes happening in the industry is one of the crucial parts in business. Lets’ Shopping is one of the mobile applications that can be downloaded through play store on the phone. The idea of this app is to make service through online applications when there are many online applications that are famous nowadays like FoodPanda, Grab, MyCar and many more. My business is focusing on services that can be served by personal shoppers. Personal shoppers get paid to shop and run errands, serving clients who are too busy or simply unable to shop for themselves. Besides, the concept that we want to propose is the current home things delivery landscape needs to be assessed in order to come up with a strategy that can make a difference towards the business.